Analysis of the Constitutional Court Decision No. 105/PPU-XXII/2024 con-cerning the Judicial Review of Law No. 1 of 2024 Article 28 Paragraph 2 re-garding the phrase "feelings of hatred and hostility" according to the Siyasah Qadhaiyyah - Abdul Hadi Musthofa; Irwansyah Irwansyah (LEGAL BRIEF, 2025)
Decision of the Constitutional Court (MK) of the Republic of Indonesia Number 105/PUU-XXII/2024. This decision is in the spotlight because it tests the constitutionality of Article 28 paragraph (2) of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law), specifically regarding the phrase "feelings of hatred or hostility." This report places the decision in the context of a broader debate regarding the protection of citizens' constitutional rights, especially freedom of expression, which is often threatened by legal formulations known as "rubber articles." The criminalization of legitimate criticism, manifested in the practice of Strategic Litigation Against Public Participation (SLAPP), has become a crucial issue that demands a strong judicial response. Thus, this decision has significant urgency as a judicial effort to guarantee basic rights and balance the protection of individual reputations with a healthy democratic space. The main objective of this report is to go beyond conventional positive law analysis by examining this MK Decision from the theoretical framework of Siyasah Qadhaiyyah. The aim is to reveal how the principles of justice in the Islamic tradition can provide a rich and in-depth perspective on the Court's decisions, particularly in balancing freedom of expression with protection from hate speech. This approach allows for the exploration of the harmony between the objectives of modern law that are oriented towards justice and the protection of human rights with the essence of justice in Islam. As a theoretical framework, Siyasah Qadhaiyyah is defined as a branch of knowledge in fiqh siy?sah that specifically discusses the regulation of laws and judicial policies established by those in power. This term is a combination of the words siy?sah which means "to regulate, manage, or rule" and qa?h?'iyyah which refers to "ruling, dispute resolution, or justice". The essence of this concept is that every policy and rule, including those related to the judiciary, must be directed towards realizing maslahah (goodness or welfare) and avoiding mafsadatan (damage or harm) for all humanity.